Rule-Based Multiple Coverage Path Planning Algorithm for Scanning a Region of Interest - Nameung Hwang; Joonwon Kim; Philjoon Jung (Drones)
This paper considers the multiple path planning problem to cover a region of interest using vertical takeoff and landing (VTOL) drones. Drones are used not only to explore unknown areas but also to view areas from the air that are difficult for people to approach by cars, boats, etc. Hence, the coverage path planning for drones should work regardless of whether the drone is inside or outside the region of interest. The proposed algorithm starts by adjusting the region of interest based on the capturing area. Once the region of interest is determined, multiple path plans are created based on the pre-derived rules for generating an optimal path under the general case and the drone’s performance, such as speed, maximum flight time, etc. The aim is to minimize the time to cover the whole region of interest. Hence, the following criteria are applied to determine the appropriateness of the generated paths: (1) whether the start and end points of the path are located as close as possible to the drone’s position, (2) whether the number of generated paths is appropriate, and (3) whether the makespan differences between the paths are small. The performance of the proposed algorithm is verified by numerous simulations.